IMF Research Bulletin, Fall-Winter 2019. (IMF Research Bulletin; IMF Research Bulletin, 2019)
It has been two years since the trade tensions erupted and not only captured policymakers' but also the research community's attention. Research has quickly zoomed in on understanding trade war rhetoric, tariff implementation, and economic impacts. The first article in the December 2019 issue sheds light on the consequences of the recent trade barriers.